Islamic Religious Education in Early Marriage Families, Case Study in Bandung Regency - Muchtarom, Muchtarom (The International Journal of Law Review and State Administration, 2024)
This research aims to determine the role and model of Islamic religious education in young married families in Banjaran Village, Bandung Regency. The research method uses a qualitative approach and uses primary and secondary data sources. Data collection techniques include observation, in-depth interviews, and documentation studies. The results of this research show that the role of Islamic religious education in young marriage families carried out in Banjaran village, Bandung Regency is that there is still minimal outreach to teenagers. This is because the majority of their education is low so in terms of Islamic religious education, those who marry at a young age only receive formal education. However, as parents of children, young people who marry are already carrying out their role as families, the first place of education for children.